Comparative transcriptional and proteomic profiling of bread wheat cv. 'Bobwhite' and its derived transgenic line over-expressing a lmw-gs gene - Scossa F.; Laudencia-Chingcuanco D.; Anderson O.D.; Vensel W.H.; Lafiandra D.; D'Ovidio R.; Masci S. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
A parallel transcriptional and proteomic comparison of seeds from a transformed bread wheat line over-expressing a transgenic low molecular weight glutenin subunit gene relative to the corresponding nontransformed genotype was performed. Proteomic analyses showed that, during seed development, several classes of endosperm proteins were differentially accumulated in the transgenic genotype. As a result of the strong increase in the amount of the transgenic protein, the endogenous glutenin subunit, all sub-classes of gliadins, and metabolic as well as Chloroform/Methanol soluble proteins were reduced in the transgenic genotype. This result was paralleled by the corresponding changes in transcript levels detected by microarray experiments. These findings suggest that the most evident effect of the strong over-expression of the transgenic glutenin gene consists in a global compensatory response involving a significant decrease in the amounts of polypeptides belonging to the prolamin superfamily.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)